Pengaruh Kedisiplinan, Lingkungan Kerja dan Budaya Kerja Terhadap Kinerja Pegawai pada Kantor Kecamatan Biringkanaya Makassar - Khalik, Abdu; Hamzah, Mukhtar; Kamaluddin, La Ode Amijaya; Sapada, Mh. Iqbal Andi (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This research aims to determine and analyze the partial or simultaneous influence of discipline, work environment and work culture on employee performance at the Biringkaya District Office, Makassar City. To find out and analyze which variables have a dominant influence on employee performance at the Biringkaya District Office, Makassar City. The data collection technique in this research is using a questionnaire and documentation as a means of obtaining accurate data and information about the variables studied. After the data is processed through a questionnaire, the data is tabulated and then the data is processed using the SPSVersion 20 program. Measurement scale in research by using a Likert Scale, the method of analysis used is the Multiple Linear Regression Analysis tool . The research results show that partially discipline, work environment and work culture have a positive and significant effect on employee performance at the Biringkaya District Office, Makassar City. Meanwhile, based on a simultaneous test of discipline, the work environment and work culture have a positive and significant effect on employee performance at the Biringkaya City District Office. The variable that has the dominant influence is the work environment variable with a beta value of 0.442 and a significance level of 0.000 < 0.005.